Atomic-scale identification of invisible cation vacancies at an oxide homointerface. (January 2021) - Kim, Y.I.; Jeong, M.; Byun, J.; Yang, S.-H.; Choi, W.; Jang, W.-S.; Jang, J.; Lee, K.; Kim, Y.; Lee, J.; Lee, E.; Kim, Y.-M.
Abstract: Cation vacancies play an important role in creating new functionalities in complex oxides. Directly identifying the cation vacancies at the atomic scale is thus key to addressing quantum phenomena related to acceptor states. Here, atomic-scale identification of invisible cation vacancies at an oxide interface via energy-dispersive X-ray spectroscopy (EDX) spectrum imaging is demonstrated. At the homointerface of SrTiO3 (STO) film and a Nb-doped SrTiO3 substrate, the veiled behavior of cation vacancies of Sr and Ti is revealed by the approach for the first time; they are found to reside on their sublattices within the first three or four unit cells of the film in the absence of oxygen vacancies. Theoretical calculations show that two-dimensional electron gas with three unit-cells at the Nb:STO/STO interface is formed by the charge transfer, which leads to the spontaneous formation of cation vacancies for charge compensation, and induces the lattice distortion as well. The results suggest that our EDX approach is useful for obtaining atomic-site-specific information on point defect chemistry with unparalleled precision, which facilitates a path towards atomically precise defect engineering. Graphical abstract: STEM-EDX chemical mapping can provide an atomic-level picture of what truly occurs with cation vacancies at an oxide interface. Cation vacancies of Sr and Ti in SrTiO3 film and Nb ions diffused from a Nb:SrTiO3 substrate are revealed to collaboratively participate in the formation of a nonstoichiometric interface layer for charge compensation, resulting in the tetragonal phase transition. Image 1 Highlights: Cation vacancies are atomically mapped out at an oxide homointerface by EDX analysis. STEM-based EDX chemical mapping with a 1-Å-level drift stability is realized for achieving atomic-level characterization. Defect-induced lattice distortion at the interface are measured with a pico-scale precision. A nonstoichiometric interface layer containing cation vacancies in SrTiO3 /Nb-doped SrTiO3  homostructure is unveiled. Very low ion diffusion from the substrate is even revealed to work with cation vacancies to achieve charge balance.